VVSH-nieuws : driemaandelijks periodiek. (Hasselt : VVSH, 1983)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijksRedactie : Kempische Steenweg 52, 3500 Hasselt ; vanaf (1985) 2 : Wijngaardstraat 1, 3500 Hasselt
Nederlands
Periodiek